PENGARUH HARGA, LOKASI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PERTANIAN DI TOKO DNA PANTURA DESA LAMONGAN KECAMATAN ARJASA KABUPATEN SITUBONDO - Rachman, Riza; Sabrina, Hunaidah; Sandy, Rizka Gabriella; Rahayu, Nita Sartika Putri; Hidayat, Robiyatul; Vinanda, Yogi Ryan (Growth, 2024)
This research aims to determine the influence of price, location and service quality on purchasing decisions for agricultural products at the Pantura DNA Shop, Congapan Lamongan Village, Arjasari District. This research uses quantitative methods with a survey approach. The research population was all consumers of the Pantura DNA Shop, totaling 3,713 people. The research sample consisted of 97 people taken using purposive sampling technique. Research data was collected through questionnaires and analyzed using multiple linear regression tests.The results of the research show that price, location and service quality have a significant influence on the decision to purchase agricultural products at the Pantura DNA Store. Price has a positive and significant effect on decisions to purchase agricultural products. Location has a positive and significant effect on decisions to purchase agricultural products. Service quality has a positive and significant effect on decisions to purchase agricultural products. Based on the research results, it is recommended that the Pantura DNA Store maintain competitive agricultural product prices, improve service quality, and expand business locations to improve purchasing decisions for agricultural products.